The effects of mechanical noise bandwidth on balance across flat and compliant surfaces - Jeshaiah, Zhen Syuen Khor; Gopalai, Alpha Agape; Boon, Leong Lan; Gouwanda, Darwin; Ahmad, Siti Anom (Nature Publishing Group, 2021)
Although the application of sub-sensory mechanical noise to the soles of the feet has been shown to enhance balance, there has been no study on how the bandwidth of the noise affects balance. Here, we report a single-blind randomized controlled study on the effects of a narrow and wide bandwidth mechanical noise on healthy young subjects’ sway during quiet standing on firm and compliant surfaces. For the firm surface, there was no improvement in balance for both bandwidths—this may be because the young subjects could already balance near-optimally or optimally on the surface by themselves. For the compliant surface, balance improved with the introduction of wide but not narrow bandwidth noise, and balance is improved for wide compared to narrow bandwidth noise. This could be explained using a simple model, which suggests that adding noise to a sub-threshold pressure stimulus results in markedly different frequency of nerve impulse transmitted to the brain for the narrow and wide bandwidth noise—the frequency is negligible for the former but significantly higher for the latter. Our results suggest that if a person’s standing balance is not optimal (for example, due to aging), it could be improved by applying a wide bandwidth noise to the feet.